The future of information and communications technology transfer in the Philippine Garments Industry through forecasting by analogy - Pamittan, Rose Anne
Few decades ago, the garment is one of the protected traded goods through the MFA quota imposed by the World Bank, Bangladesh and Philippines were two of the many developing countries that took advantage and benefited from this quota system until 2005.